The Danish girl : a novel - Ebershoff, David (Viking, 2000)
A stunning first novel that probes the mysteries of sex, gender, and love with insight and subtlety Inspired by the true story of Danish painter Einar Wegener and his California-born wife, this tender portrait of a marriage asks: What do you do when someone you love wants to change? It starts with a question, a simple favor asked of a husband by his wife on an afternoon chilled by the Baltic wind while both are painting in their studio. Her portrait model has canceled, and would he mind slipping into a pair of women's shoes and stockings for a few moments so she can finish the painting on time. "Of course," he answers. "Anything at all." With that, one of the most passionate and unusual love stories of the twentieth century begins.